Anode for all-solid-state batteries

JP7643290B2Active Publication Date: 2025-03-11TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021167821
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-13
Publication Date
2025-03-11
Estimated Expiration
2041-10-13

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、拘束圧変動を抑制可能な全固体電池用負極を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643290000003
    Figure 0007643290000003
  • Figure 0007643290000004
    Figure 0007643290000004
  • Figure 0007643290000001
    Figure 0007643290000001
Patent Text Reader

Abstract

To provide an all-solid battery anode capable of reducing restraint pressure fluctuation.SOLUTION: The present invention relates to an all-solid battery anode including an anode active material, and the anode active material contains an Si-based particle having pores. Regarding the Si-based particle having the pores, a shape parameter x expressed by an expression (1): x=p / d [wherein p defines a pore diameter (nm) of a highest existence ratio in a log differentiation pore capacity distribution curve obtained according to a DFT method of the Si-based particle and d defines an average particle diameter D50 (nm) of the Si-based particle] satisfies 0.072 or more, and a surface characteristic parameter y expressed by an expression (2): y=D1 / D2 [wherein D1 defines a peak intensity of Si2p at a position of a depth 1.3 nm from a particle surface in a case where X-ray photoelectron spectroscopy is performed on the Si-based particle and D2 defines a peak density of Si2P at a position of a depth 39 nm from the particle surface in a case where the X-ray photoelectron spectroscopy is performed on the Si-based particle] satisfies 0.697 or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a negative electrode for an all-solid-state battery. [Background technology]

[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent.

[0003] For example, Patent Document 1 discloses an all-solid-state battery having a negative electrode active material layer containing a Si-based negative electrode active material, in which the negative electrode active material layer has a specific amount of voids in a region of 0.3 μm around the surface of the Si-based negative electrode active material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-103656 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is known that Si-based negative electrode active materials are used in all-solid-state batteries. Although Si-based negative electrode active materials have a large theoretical capacity and are effective in increasing the energy density of batteries, they have a large volume change during charging and discharging, which may cause fluctuations in the confining pressure of the all-solid-state battery. If the fluctuations in the confining pressure of the all-solid-state battery become larger than the reference pressure range, the cells in the pack may not be able to be confined, causing the cells to fall, or the negative electrode active material layer may peel off or slide off, causing a short circuit. In the above-mentioned Patent Document 1, a certain effect was obtained in reducing the expansion and contraction of the Si-based negative electrode active material by forming a specific amount of voids in a region of 0.3 μm around the surface of the Si-based negative electrode active material. However, further control of the suppression of the fluctuation of the confining pressure was required.

[0006] The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide a negative electrode for an all-solid-state battery capable of suppressing fluctuations in confining pressure. [Means for solving the problem]

[0007] The negative electrode for an all-solid-state battery according to the present disclosure includes a negative electrode active material, The negative electrode active material contains Si-based particles having pores, The Si-based particles having pores are A shape parameter x represented by the formula (1): x=p / d (wherein p represents the pore size (nm) having the highest abundance ratio in a log differential pore volume distribution curve obtained by a DFT method of the Si-based particles, and d represents the average particle size D50 (nm) of the Si-based particles) is 0.072 or more, and A surface characteristic parameter y represented by the formula (2): y=D1 / D2 (wherein D1 represents the peak intensity of Si2p at a position 1.3 nm deep from the particle surface when the Si-based particle is analyzed by X-ray photoelectron spectroscopy (XPS), and D2 represents the peak intensity of Si2p at a position 39 nm deep from the particle surface when the Si-based particle is analyzed by X-ray photoelectron spectroscopy) is 0.697 or more; The negative electrode for an all-solid-state battery is characterized in that Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a negative electrode for an all-solid-state battery capable of suppressing fluctuations in confining pressure. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an all-solid-state battery according to the present disclosure. [Diagram 2] FIG. 2 is a diagram in which the values ​​of the shape parameter x and the surface characteristic parameter y of the Si-based particles having pores of Examples 1 to 6 and Comparative Examples 2 to 8 are plotted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Negative electrode for all-solid-state batteries] The negative electrode for an all-solid-state battery according to the present disclosure includes a negative electrode active material, The negative electrode active material contains Si-based particles having pores, The Si-based particles having pores are A shape parameter x represented by the formula (1): x=p / d (wherein p represents the pore size (nm) having the highest abundance ratio in a log differential pore volume distribution curve obtained by a DFT method of the Si-based particles, and d represents the average particle size D50 (nm) of the Si-based particles) is 0.072 or more, and The surface characteristic parameter y expressed by the formula (2): y=D1 / D2 (wherein D1 represents the peak intensity of Si2p at a depth of 1.3 nm from the particle surface when the Si-based particle is analyzed by X-ray photoelectron spectroscopy (XPS), and D2 represents the peak intensity of Si2p at a depth of 39 nm from the particle surface when the Si-based particle is analyzed by X-ray photoelectron spectroscopy) is 0.697 or more.

[0011] In order to obtain an all-solid-state battery negative electrode capable of suppressing the confining pressure fluctuation, the present inventors have focused on the shape parameters and surface characteristic parameters of the Si-based particles having fine pores as the raw material, and have conducted extensive research into the correlation with the confining pressure fluctuation. As a result, the present inventors have found that the shape parameter x of a specific formula (1) consisting of the main pore diameter and average particle diameter D50 value of the Si-based particles having fine pores, and the surface characteristic parameter y of a specific formula (2) consisting of the peak intensity of two types of Si2p at different depths in the XPS analysis of the Si-based particles having fine pores have a high correlation with the confining pressure fluctuation, as shown in the examples and comparative examples described later, and have completed the present invention. In the present disclosure, by controlling the Si-based particles having pores such that the shape parameter x of the formula (1) is 0.072 or more and the surface characteristic parameter y of the formula (2) is 0.697 or more, which are highly correlated with the variation in the confining pressure, a battery negative electrode capable of suppressing the variation in the confining pressure can be provided.

[0012] The negative electrode for an all-solid-state battery disclosed herein includes a negative electrode active material, and the negative electrode active material includes Si-based particles having the specific pores.

[0013] The negative electrode active material may be a Si-based negative electrode active material. Examples of the Si-based negative electrode active material include simple Si, Si alloys, and Si oxides. The Si alloy preferably contains Si element as a main component. The ratio of Si element in the Si alloy may be, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. Examples of the Si alloy include Si-Li-based alloys, Si-Al-based alloys, Si-Sn-based alloys, Si-In-based alloys, Si-Ag-based alloys, Si-Pb-based alloys, Si-Sb-based alloys, Si-Bi-based alloys, Si-Mg-based alloys, Si-Ca-based alloys, Si-Ge-based alloys, and Si-Pb-based alloys. The Si alloy may be a two-component alloy or a multi-component alloy of three or more components. The Si alloy may be a Si-Li-based alloy.

[0014] The Si-based negative electrode active material may be in the form of particles. In the present disclosure, particulate Si-based negative electrode active material is referred to as Si-based particles. The Si-based particles used in the present disclosure may have specific pores. The Si-based particles having pores used in the present disclosure satisfy the shape parameter x expressed by the formula (1): x = p / d of 0.072 or more, and the surface property parameter y expressed by the formula (2): y = D1 / D2 of 0.697 or more. It is presumed that the Si-based particles having pores used in the present disclosure can reduce the expansion and contraction of the Si-based negative electrode active material and can control the suppression of the confining pressure fluctuation.

[0015] In the formula (1), p represents the pore diameter (nm) having the highest abundance ratio in the log differential pore volume distribution curve obtained by the DFT method of the Si-based particles having the pores. p can be measured using a specific surface area measuring device for the Si-based particles having the pores. As a specific method for determining the pore diameter having the highest abundance ratio of the Si-based particles having the pores of the present disclosure, the method described in the examples described later can be adopted. The Si-based particles having pores used in the present disclosure may have a pore size with the highest abundance ratio of 39.5 nm to 47.5 nm in a log differential pore volume distribution curve obtained by a DFT method.

[0016] In the formula (1), d represents the average particle diameter D50 (nm) of the Si-based particles. The average particle diameter D50 is the cumulative 50% particle diameter D in the volume-based particle diameter distribution measured by a laser diffraction particle size distribution measuring device. 50 As a specific method for determining the average particle diameter D50 of the Si-based particles having pores according to the present disclosure, the method described in the Examples section below can be adopted. The Si-based particles having pores used in the present disclosure may have an average particle size D50 of 331 nm to 660 nm, or may be 331 nm to 389 nm.

[0017] The Si-based particles having pores according to the present disclosure have a shape parameter x expressed by the formula (1): x = p / d of 0.072 or more. The upper limit of x is not particularly limited, but may be 0.144 or less. The lower limit of x may be 0.110 or more. Regarding the shape parameter x, when the pore diameter is large relative to the grain diameter, the confining pressure fluctuation tends to be low. It is presumed that the size of the pores in the Si-based particles having pores is effective in relaxing stress.

[0018] In formula (2), D1 represents the peak intensity of Si2p at a depth of 1.3 nm from the particle surface when the Si-based particle having the pores is analyzed by XPS, and D2 represents the peak intensity of Si2p at a depth of 39 nm from the particle surface when the Si-based particle having the pores is analyzed by XPS. The positions at depths of 1.3 nm and 39 nm from the particle surface are respectively SiO 2 This is calculated as the sputtering rate. D1 and D2 each represent the chemical bond state (Si2p orbital) near the surface of the Si-based particle having a pore, and can be determined by depth profile analysis using XPS. As a specific method for determining D1 and D2 of the Si-based particle having a pore of the present disclosure, the method described in the examples below can be adopted. In the Si-based particles having pores used in the present disclosure, the D1 may be 28.5 to 33.4, and the D2 may be 27.6 to 45.2.

[0019] The Si-based particles having pores according to the present disclosure satisfy the surface characteristic parameter y expressed by the formula (2): y = D1 / D2 of 0.697 or more. The upper limit of y is not particularly limited, but may be 1.211 or less. The lower limit of y may be 0.716 or more. Regarding the surface characteristic parameter y, there is a tendency for the confining pressure fluctuation to be lower when the Si2p peak intensity at a depth of 1.3 nm is higher than the Si2p peak intensity at a depth of 39 nm from the particle surface. It is presumed that the reactivity due to the crystallinity of the surface of Si-based particles with pores or the stress absorption due to the reduced internal strength affect the reduction in the confining pressure fluctuation. However, in the Si-based particles having the pores of the present disclosure, both the shape parameter x and the surface characteristic parameter y must satisfy the above ranges, and it is presumed that there is a correlation between the confining pressure fluctuation and both.

[0020] In addition, the Si-based particles having the pores of the present disclosure have a specific surface area (m 2 / g) is 24.8 to 51.0 m 2 / g, 24.8 to 38.8m 2 / g. The specific surface area (m 2 / g) can be measured using a specific surface area measuring device, and as a specific method for determining it, the method described in the Examples below can be adopted.

[0021] The method for producing the Si-based particles having pores of the present disclosure is not particularly limited as long as the shape parameter x and surface property parameter y are satisfied. The method for producing the Si-based particles having pores of the present disclosure may be a production method having the following steps 1 to 6, since it can easily produce Si-based particles having pores that simultaneously satisfy the parameters x and y. The production method having the following steps 1 to 6 can easily produce Si-based particles having pores that simultaneously satisfy the parameters x and y by particularly including the following step 3.

[0022] Step 1: A step of pulverizing a Si-based negative electrode active material in a ball mill and adjusting the particle size to a predetermined particle size to obtain Si-based particles. Step 2: A step of placing the obtained Si-based particles in a mortar, adding metallic Li, and mixing the powder at room temperature to obtain Si-Li-based alloy particles. Step 3: A step of adding Si-Li alloy particles to a mesitylene solvent, and then adding dropwise ethanol at 0°C or lower at a constant rate while stirring the mixture at room temperature (25°C). Step 4: Further adding acetic acid dropwise at a constant rate while stirring the mixture. Step 5: filtering the resulting mixture under reduced pressure to recover the powder. Step 6: A step of vacuum drying the recovered powder to remove the solvent and obtain Si-based particles having pores.

[0023] The composition of the Si negative electrode active material, the amount of the Si negative electrode active material, the ball mill rotation speed, and the pulverization time can be appropriately controlled in the step 1. The predetermined particle size can be adjusted to, for example, 300 to 2000 nm.

[0024] The amount of metallic Li, the rotation speed of the mortar, and the mixing time can be appropriately controlled in the step 2. The amount of metallic Li can be adjusted to, for example, 0.8 to 1.4 (mass ratio) relative to the Si-based particles.

[0025] In the step 3, the amount of mesitylene, the temperature of ethanol, the dropping speed, the amount of ethanol, and the rotation speed of the stirrer can be appropriately controlled. The amount of mesitylene can be adjusted to, for example, 25 to 45 (mass ratio) relative to the Si-Li alloy particles. The ethanol temperature can be adjusted to, for example, 0°C or lower. The dropping speed of ethanol can be adjusted to, for example, 1 drop / 2 sec to 1 drop / 6 sec. The amount of ethanol can be adjusted to, for example, 0.8 to 1.4 (mass ratio) relative to the Si-Li alloy particles. The rotation speed of the stirrer can be adjusted to, for example, 100 to 500 (unit: rpm). In the step 3, by adding mesitylene to the Si-Li alloy particles in advance, the reactivity of ethanol with the Si-Li alloy particles can be controlled, and the fine pore structure can be controlled.

[0026] The amount of acetic acid and the rotation speed of the stirrer can be appropriately controlled in the step 4. The amount of acetic acid can be adjusted to, for example, 45 to 65 (mass ratio) relative to the Si-Li alloy particles.

[0027] The degree of vacuum during vacuum drying and the drying time can be appropriately controlled in step 6. The degree of vacuum may be, for example, −0.1 MPa, and the drying time may be 12 hours or more.

[0028] The negative electrode for an all-solid-state battery according to the present disclosure may further contain other components in addition to the negative electrode active material. The negative electrode for the all-solid-state battery of the present disclosure may have a negative electrode active material layer on one or both sides of a negative electrode current collector. The negative electrode current collector may have a thickness of, for example, 5 μm to 30 μm. Examples of the material for the negative electrode current collector include SUS, copper, and nickel.

[0029] The negative electrode active material layer may contain at least one of a solid electrolyte, a conductive material, and a binder, in addition to the negative electrode active material, as necessary. The proportion of the negative electrode active material in the negative electrode active material layer is, for example, 20 mass % or more, or may be 30 mass % or more, or may be 40 mass % or more, while the proportion of the negative electrode active material is, for example, 80 mass % or less, or may be 70 mass % or less, or may be 60 mass % or less. The negative electrode active material layer may contain only the Si-based particles having the pores as the negative electrode active material, or may contain other negative electrode active materials. In the latter case, the ratio of the Si-based particles having the pores to the total negative electrode active material may be 50 mass % or more, 70 mass % or more, or 90 mass % or more.

[0030] Examples of the solid electrolyte include a sulfide solid electrolyte and an oxide solid electrolyte. Examples of sulfide solid electrolytes include solid electrolytes containing Li, X (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and halogen elements. Examples of halogen elements include F, Cl, Br, and I.

[0031] The sulfide solid electrolyte preferably comprises an ion conductor containing Li, A (A is at least one of P, As, Sb, Si, Ge, Al, and B), and S. Furthermore, the ion conductor preferably has a high Li content.

[0032] The sulfide solid electrolyte may contain a lithium halide in addition to the ion conductor. Examples of the lithium halide include LiF, LiCl, LiBr, and LiI, and among them, LiCl, LiBr, and LiI are preferred. The proportion of LiX (X=F, I, Cl, Br) in the sulfide solid electrolyte is, for example, 5 mol% or more, and may be 15 mol% or more. On the other hand, the proportion of LiX is, for example, 30 mol% or less, and may be 25 mol% or less.

[0033] A specific example of a sulfide solid electrolyte is xLi 2 S·(100-x)P 2 S 5 (70≦x≦80), yLiI・zLiBr・(100-yz)(xLi 2 S (1-x)P 2 S 5 ) (0.7≦x≦0.8, 0≦y≦30, 0≦z≦30). The sulfide solid electrolyte is 10LiI-15LiBr-75 (0.75Li 2 S-0.25P 2 S 5 ) may be.

[0034] As the oxide solid electrolyte, for example, Li 2 Alumni 2 O 3 -P 2 O 5 , Li 2 O-SiO 2 , LiLaTaO (e.g. Li 5 La 3 Ta 2 O 12 ), LiLaZrO (e.g. Li 7 La 3 Zr 2 O 12 ), LiBaLaTaO (e.g. Li 6 Bala 2 Ta 2 O 12 ), Li 1+x S x P 1-x O 4 (0≦x<1, e.g., Li 3.6 S 0.6 P 0.4 O 4 ), Li 1+x Al x Ge 2-x (PO 4 ) 3 (0≦x≦2), Li 1+x Al x Ti 2-x (PO 4 ) 3 (0≦x≦2), Li 3 PO (4-3 / 2x) Nx (0≦x<1) etc.

[0035] Examples of the conductive material include carbon materials. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fiber, carbon nanotubes (CNT), carbon nanofibers (CNF), and vapor grown carbon fiber (VGCF). The conductive material may be vapor grown carbon fiber (VGCF).

[0036] Examples of the binder include rubber-based binders such as butylene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVDF). The binder may be polyvinylidene fluoride (PVDF).

[0037] The thickness of the negative electrode active material layer is, for example, 0.3 μm or more and 1000 μm or less.

[0038] The negative electrode for an all-solid-state battery according to the present disclosure contains a negative electrode active material. As long as the negative electrode active material contains Si-based particles having the specific pores, the negative electrode can be produced by appropriately selecting a conventionally known production method.

[0039] [All-solid battery] FIG. 1 is a schematic cross-sectional view showing an example of an all-solid-state battery according to the present disclosure. The all-solid-state battery 100 includes a battery element 20. The all-solid-state battery 100 may further include an exterior body (not shown). The battery element 20 may be housed in the exterior body. The exterior body may be, for example, a metal case or the like. The exterior body may be, for example, a pouch made of an aluminum laminate film or the like.

[0040] The battery element 20 includes a positive electrode 11, a solid electrolyte layer 13, and a negative electrode 12. The positive electrode 11 includes a positive electrode active material and a solid electrolyte. The negative electrode 12 is the negative electrode for an all-solid-state battery of the present disclosure. The solid electrolyte layer (separator layer) 13 is interposed between the positive electrode 11 and the negative electrode 12. The solid electrolyte layer 13 blocks electronic conduction between the positive electrode 11 and the negative electrode 12. The solid electrolyte layer 13 conducts ions. That is, the solid electrolyte layer 13 ionically connects the positive electrode 11 and the negative electrode 12. The positive electrode 11 and the solid electrolyte layer 13 can be appropriately selected from conventionally known positive electrodes and solid electrolyte layers for all-solid-state batteries. Specific examples of the positive electrode 11 and the solid electrolyte layer 13 include those described in JP-A-2021-103656.

[0041] The all-solid-state battery in the present disclosure may be an all-solid-state lithium battery. The all-solid-state battery may be a primary battery or a secondary battery, and in particular may be a secondary battery. This is because the battery can be repeatedly charged and discharged, and is useful, for example, as an in-vehicle battery. The secondary battery also includes a secondary battery used as a primary battery (used only for the purpose of initial charging).

[0042] The all-solid-state battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a parallel-connected stacked battery) or a bipolar stacked battery (a series-connected stacked battery). The shape of the all-solid-state battery may be, for example, a coin type, a laminate type, a cylindrical type, or a square type. EXAMPLES

[0043] EXAMPLES The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0044] [Example 1] (Preparation of Si-based particles with fine pores) Step 1: The Si active material (composition: Si metal) was pulverized in a ball mill (rotation speed: 1000 rpm, time: 3 hours) and adjusted to a predetermined particle size (600 nm) to obtain Si-based particles. Step 2: The obtained Si-based particles were placed in a mortar, and metallic Li was added. The powder was mixed at room temperature (mortar rotation speed: 50 rpm, time: 20 minutes) to obtain a Si-Li-based alloy. The Si-based particles and metallic Li were weighed out so that they were contained in the mixture in a mass ratio of Si-based particles:metallic Li = 1:1.2. Step 3: After adding a Si-Li alloy (0.1 part by mass) to 3.4 parts by mass of mesitylene solvent, the mixture was stirred (stirrer rotation speed: 250 rpm) at room temperature (25°C), and ethanol (0.1 part by mass) at -5°C was added dropwise at a constant rate (1 drop / 5 sec). Step 4: While the mixture was being stirred (stirrer rotation speed: 250 rpm), acetic acid (5.6 parts by mass) was added dropwise at a constant rate (1 drop / 5 sec). Step 5: The resulting mixture was filtered under reduced pressure to recover the powder. Step 6: The powder was vacuum-dried (vacuum degree: -0.1 MPa, drying time: 12 hours) to remove the solvent, and Si-based particles having pores were obtained.

[0045] (Preparation of negative electrode) The above-mentioned porous Si-based particles were mixed with 50 mass% of a sulfide solid electrolyte (10LiI-15LiBr-75(0.75Li 2 S-0.25P 2 S 5 )), 10% by mass of conductive material (VGCF), and 3% by mass of binder (PVdF) were added to a dispersion medium (heptane). This dispersion medium was subjected to ultrasonic treatment for 5 minutes using an ultrasonic homogenizer to obtain a negative electrode composite material. The negative electrode composite material was applied to both sides of a current collector foil (Ni foil, thickness 24 μm), dried, and then roll pressed at a linear pressure of 50 kN / cm. The obtained current collector foil with negative electrode active material layers (thickness of each layer: 45.3 μm) was punched out to φ11.3 mm (1 cm 2 ) to obtain a negative electrode.

[0046] (Preparation of evaluation battery) Cathode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2) in 84.7% by mass, sulfide solid electrolyte (10LiI-15LiBr-75(0.75Li 2 S-0.25P 2 S 5 )), 1.3 mass% of conductive material (VGCF), and 0.6 mass% of binder (PVdF) were added to a dispersion medium (heptane). This dispersion medium was subjected to ultrasonic treatment for 5 minutes using an ultrasonic homogenizer to obtain a positive electrode composite material. The positive electrode composite material was applied to a current collector foil (Al foil, thickness 10 μm) and dried, and then roll pressed at a linear pressure of 50 kN / cm. The obtained current collector foil with a positive electrode active material layer (thickness 70.0 μm) was punched out to φ11.3 mm (1 cm 2 ) to obtain a positive electrode.

[0047] Sulfide solid electrolyte (10LiI-15LiBr-75(0.75Li 2 S-0.25P 2 S 5 )) and 0.5% by mass of binder (PVdF) were added to a dispersion medium (heptane). This dispersion medium was subjected to ultrasonic treatment for 5 minutes using an ultrasonic homogenizer to obtain a composite material. The obtained composite material was applied to a substrate (Al foil, thickness 20 μm) to a thickness of 15 μm and dried, and then punched out to a diameter of Φ11.3 mm (1 cm 2 ) and a solid electrolyte layer (separator layer, thickness 15.0 μm) were obtained.

[0048] The positive electrode, separator layer, and negative electrode were stacked together with their centers aligned, and a surface pressure of 5 tons / cm was applied. 2 The layers were then sealed with a tabbed laminate and restrained at 5 MPa to produce an evaluation battery (all-solid-state lithium battery). The evaluation battery was produced to have a capacity of 2 mAh.

[0049] [Examples 2 to 6] In step 3 of the preparation of Si-based particles having fine pores in Example 1, Si-based particles having fine pores were prepared in the same manner as in Example 1, except that at least one of the amount of mesitylene, the temperature of ethanol, the dropping rate of ethanol, the amount of ethanol, and the rotation speed of the stirrer was changed. A negative electrode and a battery for evaluation were produced in the same manner as in Example 1 using the obtained Si-based particles having fine pores.

[0050] [Comparative Example 1] A negative electrode and a battery for evaluation were produced in the same manner as in Example 1, except that in the production of the negative electrode of Example 1, Si-based particles without pores were used instead of the Si-based particles with pores.

[0051] [Comparative Examples 2 to 8] In step 3 of the preparation of Si-based particles having fine pores in Example 1, Si-based particles having fine pores were prepared in the same manner as in Example 1, except that at least one of the amount of mesitylene, the temperature of ethanol, the dropping rate of ethanol, the amount of ethanol, and the rotation speed of the stirrer was changed. A negative electrode and a battery for evaluation were produced in the same manner as in Example 1 using the obtained Si-based particles having fine pores.

[0052] [evaluation] (Pore size and specific surface area of ​​Si-based particles) The adsorption isotherm of the Si-based particles was measured by a nitrogen gas adsorption method at a gas liquefaction temperature of 77K using a specific surface area measuring device (Quantachrome Nova, manufactured by Anton Paar QuantaTec). Using the obtained adsorption isotherm, the pore diameter (nm) with the highest abundance ratio was determined in the log differential pore volume distribution curve obtained by the DFT method, and the specific surface area of ​​the Si-based particles was calculated by the BET method using the obtained adsorption isotherm. The measurement results of Examples 1 to 6 and Comparative Examples 1 to 8 are shown in Table 1 or Table 2.

[0053] (Average particle size D50 of Si-based particles) The Si-based particles were dispersed in a water solvent by a wet method, and the cumulative 50% particle diameter D50 in the volume-based particle diameter distribution was determined using a laser diffraction particle diameter distribution analyzer (SALD-2300, manufactured by SHIMADZU). The measurement results of Examples 1 to 6 and Comparative Examples 1 to 8 are shown in Table 1 or Table 2.

[0054] (Depth profiling of Si particles using XPS) The analysis of the Si-based particles by XPS was performed in the depth direction by sputter etching with Ar ions using an X-ray photoelectron spectrometer (PHI X-tool, manufactured by ULVAC-PHL, INC.). The Ar ion sputtering rate was about 1.3 nm / min. The measurement results of Examples 1 to 6 and Comparative Examples 1 to 8 are shown in Tables 1 and 2. <Measurement conditions> X-ray source:AlKα X-ray conditions: 15kV, 44W Analysis range: 217μm Analysis angle: 45° Neutralization gun conditions: 1.2 eV, 20.0 μA Si2p range: 114.00-94.00eV Pass energy: 280 eV Step size: 0.500eV

[0055] (Change in confining pressure) The variation in the binding pressure was measured using a load cell. Four cells of the evaluation batteries obtained in Examples 1 to 6 and Comparative Examples 1 to 8 were bound in one jig, and a charge / discharge test was performed. The conditions of the charge / discharge test were a binding pressure (fixed size) of 5 MPa, a charge of 0.1 C, a discharge of 1 C, and a cutoff voltage of 3.1 V to 4.1 V, and the initial charge capacity and the initial discharge capacity were obtained. In addition, the binding pressure of the evaluation battery was monitored during the initial charge, and the binding pressure at 4.1 V was measured, and the increase in the binding pressure from the state before the charge / discharge was obtained. Furthermore, the normalized binding pressure variation was obtained using the following formula. Confining pressure increase / (number of cells x cell volume) = normalized confining pressure change (ΔMPa / mAh) <Judgment criteria> ○: Normalized confining pressure fluctuation is 0.30MPa / mAh or less ×: Normalized confining pressure fluctuation exceeds 0.30MPa / mAh The measurement results of Examples 1 to 6 and Comparative Examples 1 to 8 are shown in Table 1 or Table 2.

[0056] [Table 1]

[0057] [Table 2]

[0058] In Tables 1 and 2, np-Si indicates Si-based particles having pores.

[0059] FIG. 2 is a diagram in which the values ​​of the shape parameter x and the surface characteristic parameter y of the Si-based particles having pores of Examples 1 to 6 and Comparative Examples 2 to 8 are plotted. As is clear from the performance evaluation results in Figure 2 and Tables 1 and 2, in Si-based particles with pores, controlling the shape parameter expressed by x = p / d and the surface characteristic parameter expressed by y = D1 / D2 in parallel has a high correlation with the confining pressure fluctuation. It was confirmed that a negative electrode for an all-solid-state battery containing Si-based particles having fine pores as a negative electrode active material, in which the shape parameter x expressed by x=p / d is 0.072 or more and the surface property parameter y expressed by y=D1 / D2 is 0.697 or more, enables the reduction of the confining pressure fluctuation. According to the present disclosure, the influence of the parameters of Si-based particles, the contribution of which to the reduction of confining pressure fluctuations was unclear, has been clarified, and it has become possible to control the reduction of confining pressure fluctuations by controlling in parallel the shape parameter expressed by x=p / d and the surface characteristic parameter expressed by y=D1 / D2.

Claims

[Claim 1] A negative electrode active material is included, The negative electrode active material contains Si-based particles having pores, The Si-based particles having pores are The shape parameter x represented by the formula (1): x = p / d (wherein p represents the pore diameter (nm) having the highest abundance ratio in a log differential pore volume distribution curve obtained by a DFT method of the Si-based particles, and d represents the average particle diameter D50 (nm) of the Si-based particles) satisfies 0.144, the average particle diameter D50 (nm) of the Si-based particles is 331 nm, and A surface characteristic parameter y represented by the formula (2): y = D1 / D2 (wherein D1 represents the peak intensity of Si2p at a position at a depth of 1.3 nm from the particle surface when the Si-based particle is subjected to X-ray photoelectron spectroscopy, and D2 represents the peak intensity of Si2p at a position at a depth of 39 nm from the particle surface when the Si-based particle is subjected to X-ray photoelectron spectroscopy) satisfies 1.211; Negative electrode for all-solid-state batteries.

Citation Information

Patent Citations

  • Electroactive materials for metal-ion batteries

    JP2017533533A

  • All-solid lithium ion secondary battery

    JP2018073513A

  • Negative electrode active material, manufacturing method thereof, and battery

    JP2021022554A

  • All-solid battery and manufacturing method thereof

    JP2021103656A

  • Manufacturing method of porous silicon grain, manufacturing method of electrode for electricity storage device, manufacturing method of whole solid lithium ion secondary battery, porous silicon grain, electrode for electricity storage device, and whole solid lithium ion secondary battery

    JP2021123517A